The Analysis Of Renal Human Stones By FTIR Spectroscopy‌ - AL-Kefaei , Ghadaq Hameed Neamah; AL-Huchaimi, Sarah Hasan Kadhum; Alameedy, Bashaer Ahmed (Medical Science Journal for Advance Research, 2022)
Through the samples gathered we noticed the quantity of guys with kidney stones is 188, with a pace of 72.3%. Concerning the quantity of females with kidney stones, 72, with a pace of 27.7%. We additionally noticed that the ages from 1 to 20 years are 17 contaminated individuals, and ages from 20 to 30 years, their numbers are around 52 individuals, and ages from 30 to 40 years, their numbers are around 68 individuals, and ages from 40 to 50 years, their numbers are around 51 individuals. Concerning the ages north of 50 years, the level of their numbers is a lot higher than the quantities of the previously mentioned, it is around 72 individuals with kidney stones, and they are more helpless to disease... Concerning the sorts and level of stones, we saw that whewellite stones are the most various, numbering 140, uric corrosive, 56, weddellite 25, carbonate apatite26, while cystine and struvite range in numbers from 6 to 7.